Kay Wuqijin, o Alaala ng Pagsasanay sa Pagsasalin at Pagkakaibigan - Samar, Edgar Calabia (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 01 (2022): LIKHAAN 16: The Journal of Contemporary Philippine Literature, 2023)
“Kay Wuqijin, o Alaala ng Pagsasanay sa Pagsasalin at Pagkakaibigan” (trans. “For Wuqijin, or Memories of Exercises on Translation and Friendship“) is a personal essay about my brief and interrupted friendship with a Chinese student I met on my first travel outside the Philippines to China more than a decade ago. The essay includes my attempts to translate my early poetry to English for a singular reader and my thoughts on the effect that such clarity of a particular audience had on my choice of words.